FUNDUS AUTOFLUORESCENCE IN EXTENSIVE MACULAR ATROPHY WITH PSEUDODRUSEN AND DIFFUSE TRICKLING GEOGRAPHIC ATROPHY. Issue 5 (May 2023) - Bianco, Lorenzo; Antropoli, Alessio; Arrigo, Alessandro; Berni, Alessandro; La Franca, Lamberto; Saladino, Andrea; Bandello, Francesco; Battaglia Parodi, Maurizio
Abstract : Extensive macular atrophy with pseudodrusen shows remarkable clinical and imaging similarities with the diffuse-trickling pattern of geographic atrophy. Using a quantitative approach, we investigated whether extensive macular atrophy with pseudodrusen and diffuse-trickling pattern of geographic atrophy can be distinguished using blue-light autofluorescence. Abstract : Purpose: To establish whether extensive macular atrophy with pseudodrusen (EMAP) can be distinguished from the diffuse-trickling phenotype of geographic atrophy (DTGA) secondary to age-related macular degeneration on the basis of its features on blue-light autofluorescence. Methods: The authors reviewed our prospectively maintained database to enroll patients with a diagnosis of EMAP, DTGA, and non-DTGA with a minimum follow-up of 1 year. Atrophic areas and growth rates were measured on blue-light autofluorescence images, using the Heidelberg Region Finder tool. Circularity and roundness were chosen as atrophy shape descriptors, extracted using ImageJ, and compared between disease groups. Results: A total of 28 EMAP, 27 DTGA, and 30 non-DTGA eyes were included in the analysis. The median follow-up time was around 3.5 years. Extensive macular atrophy with pseudodrusen was characterized by an irregular and elongated shape (low circularity and low roundness) and associated with a fast atrophy growth rate (3.6 mm 2 /year), compared with non-DTGA. However, these parameters were not significantly different between EMAP and DTGA. Conclusion: Our study found that EMAP and DTGA cannot be effectively differentiated on fundus autofluorescence. In both diseases, the macular atrophic area has a major vertical axis, fringed borders, and fast progression.